49-3x=7

Simple and best practice solution for 49-3x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49-3x=7 equation:



49-3x=7
We move all terms to the left:
49-3x-(7)=0
We add all the numbers together, and all the variables
-3x+42=0
We move all terms containing x to the left, all other terms to the right
-3x=-42
x=-42/-3
x=+14

See similar equations:

| 14a-7=7 | | m=-3(1,5) | | ((1/2×x)+4)+((3/4×x)-6)=2x-47 | | 25x-120=1000 | | -2(3x+5)=-5-7x | | 63=3x+3(2x-15) | | B^2=-9b | | -n+8+5n=16 | | 3c-30=27 | | -7k+19k+-16=8 | | 2/x=6/100 | | 3x+27=4x+16 | | -2(4+5r)-4r=-120 | | 3(5x)+2=7x+11 | | (3/4)d=36 | | 0.2(4x-0.1)=0.06 | | -1+3/2y=8 | | 3x–6=x–2 | | -12=3-2p-3p | | -1+32y=8 | | 2x+12+2x+5+7x-1=180 | | 3v-30=v-15 | | -6k-6=102 | | 8=0.5e3 | | 3x-4=9x+44. | | ((1/2+x)+4)+((3/4+x)-6)=2x-47 | | 9x/3=33,x= | | x/7-12=13 | | 2.1c=27.3 | | 3x-6/x+1=0 | | 3x+2(5x-15)=50 | | 7m+6=-55 |

Equations solver categories